2016
DOI: 10.47210/bjohns.2016.v24i1.66
|View full text |Cite
|
Sign up to set email alerts
|

Community Awareness - A Key to the Early Detection of Head and Neck Cancer

Abstract: INTRODUCTION Mortality and morbidity associated with head and neck cancers have decreased to a great extent in many developed countries of the world due to early diagnosis and treatment with advances in surgical techniques and better availability of radiotherapist and oncologists. But the situation in developing countries like India is quite different. AIMS AND OBJECTIVES This study was conducted amongst the patients attending the Otolaryngology department of a teaching hospital in Kolkata to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Therefore, knowledge of health and the behavior of seeking appropriate public health services is very important to decrease mortality due to head and neck cancers. 11 Several studies have been conducted in America gauge the public's awareness and knowledge of HNC. The study showed that there is a gap in the knowledge of American Indians about the risk factors and symptoms of HNC.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, knowledge of health and the behavior of seeking appropriate public health services is very important to decrease mortality due to head and neck cancers. 11 Several studies have been conducted in America gauge the public's awareness and knowledge of HNC. The study showed that there is a gap in the knowledge of American Indians about the risk factors and symptoms of HNC.…”
Section: Introductionmentioning
confidence: 99%